ADMINISTRATIVE FACTORS AFFECTING SCHOOL EFFICIENCY UNDER THE SECONDARY EDUCATIONAL SERVICE OFFICE NAKHON PHANOM - Rattanakosin, Arepakorn; Piasa , Eakkalak; Pengsawat, Waro (Journal of Graduate School Sakon Nakhon Rajabhat University, 2025)
The research aimed to study administrative factors affecting school efficiency under the Secondary Educational Service Area Office Nakhon Phanom. The sample group, obtained through a multi–stage random sampling, consisted of 325 participants, including school administrators and teachers working under the Secondary Educational Service Area Office Nakhon Phanom. The sample was also determined by a Krejcie and Morgan table. The research instrument included a set of 5–rating scale questionnaires: a questionnaire on administrative factors affecting school efficiency, with a content validity index ranging from 0.60 to 1.00, the discrimination power index ranging from 0.37 to 0.87, and the reliability of 0.99, and a questionnaire on school efficiency with a content validity index ranging from 0.80 to 1.00, the discrimination power index ranging from 0.36 to 0.81, and the reliability of 0.98. Statistics for data analysis were frequency, percentage, mean, and standard deviation, Pearson’s product–moment correlation coefficient, and Stepwise multiple regression analysis. The findings were as follows. 1. The administrative factors in schools were overall at a high level. 2. The school efficiency was overall at a high level. 3. The relationship between administrative factors and school efficiency demonstrated a highly positive relationship (rxy = .89), with the .01 level of significance. 4. The administrative factors regarding teachers’ performance motivation, budget, and Information Technology affected the school efficiency at the .01 level of significance, while personnel development and organizational atmosphere and culture influenced the effectiveness of school administration at the .05 level of significance, with the predictive power of 83.40 percent. The predictive equation could be written in the form of raw and standardized scores: Y= .129+.128 (X3)+.199 (X5)+.094 (X6)+.279 (X7)+ 265 (X8). ZY= .126 (Z3)+.209 (Z5)+.095 (Z6)+.274 (Z7)+.280 (Z8) 5. The guidelines for developing the administrative factors that affected the school efficiency in schools under the Secondary Educational Service Area Office Nakhon Phanom involved five aspects: 1) Personnel Development, 2) Information Technology, 3) Organizational Atmosphere and Culture, 4) Budget, and 5) Teacher Performance Motivation.